MALFORMATION RISKS OF ANTIEPILEPTIC DRUG MONOTHERAPIES IN PREGNANCY. Issue 11 (9th October 2013) - Campbell, Ellen; Kennedy, Fiona; Irwin, Beth; Morrison, Patrick; Delanty, Norman; Hunt, Stephen; Craig, John; Morrow, Jim
Abstract : Aim: To assess risk of major congenital malformations (MCMs) from exposure to anti–epileptic drugs (AEDs) during pregnancy. Methods: Fifteen year prospective observational study from 1996 until 2012. Outcomes are reported for valproate, carbamazepine, lamotrigine and levetiracetam monotherapy exposures. Main outcome measure is the MCM rate. Results: Informative outcomes were available for 5510 cases. 1290 women were exposed to valproate monotherapy, 1718 to carbamazepine monotherapy, 2198 to lamotrigine monotherapy and 304 to levetiracetam monotherapy. The MCM risk with valproate monotherapy exposure in–utero is 6.7% (95% CI 5.5%–8.3%), compared to 2.6% with carbamazepine (95% CI 1.9%–3.5%), 2.3% with lamotrigine (95% CI 1.8%–3.1%) and 0.70% (95% CI 0.2%–2.5%) with levetiracetam. A significant dose effect is seen with valproate (p= 0.0006) and carbamazepine (p=0.03) exposed pregnancies, but not with exposure to lamotrigine (p=0.26) or levetiracetam (p=0.09). MCM rate for even the highest doses of lamotrigine (>400 mg daily) were lower than the MCM rate observed in pregnancies exposed to less than 600 mg daily of valproate (3.4% compared to 5.0%, p=0.35). Conclusions: AED exposure during pregnancy increases the risk of MCM in the infants of women with epilepsy. In utero exposure to valproate carries a significantly higher MCM risk than lamotrigine (p=0.0001), levetiracetam (p=0.0001) or carbamazepine (p=0.0001) monotherapy. Our results are in contrast to previous suggestions that the MCM risk with exposure to low doses of valproate is preferable to that seen with exposure to high doses of lamotrigine. Together with recently published neurodevelopmental data, this data suggests that either lamotrigine or levetiracetam should be used as drugs of choice over valproate, even at low dose, in women of childbearing age with epilepsy.